Genetic analysis of spontaneous resistance to ampicillin in Neisseria gonorrhoeae. - Jones, F (1985)
Step-wise intrinsic resistance to ampicillin in Neisseria gonorrhoeae was analyzed genetically by DNA-mediated transformation experiments. A first-step ampicillin-resistant (Ampr1) mutant and a second-step ampicillin-resistant (Ampr2) mutant generated during sequential selection were used in these studies. Each selection step was accompanied by an approximate twofold increase in resistance. Four amp alleles were found to account for full resistance of the Ampr2 phenotype. All four amp alleles lie among a cluster of genes which code for ribosomal functions. This region has the map order rif str fus tet cam. First-step resistance was caused by two amp alleles, ampA2 and ampB1, neither of which independently caused detectable ampicillin resistance. Outcrossing of the ampA2 or the ampB1 mutation resulted in wild-type susceptibility to ampicillin. Mapping studies indicate that ampB1 lies between str and fus, whereas ampA2 lies to the right of cam. Second-step resistance required two mutations, ampC3 and ampD4, in addition to ampB1 and ampA2. Transformation of ampC3 to ampC3+ in an Ampr2 mutant resulted in the Ampr1 phenotype. Both ampC3 and ampD4 showed transformation linkage to rif and str. ampC3 was positioned at a site between rif and str. ampD4 apparently occupied a site, outside of the rif-str region, proximal to rif and distal to str. We postulate the gene order to be ampD rif ampC str ampB fus tet cam ampA.